2019
DOI: 10.1002/ams2.410
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings on whole‐body computed tomography in trauma patients: the current state of incidental findings and the effect of implementation of a feedback system

Abstract: Aim Whole‐body computed tomography (CT) for trauma occasionally reveals significant incidental findings not related to trauma, which require an adequate response. In this study, we examined the current state of incidental findings in trauma patients on whole‐body CT and the effects of the feedback system. Methods The subject sample included trauma patients who underwent whole‐body CT while being examined for trauma during the 2‐year period, with the interpretation of the CT reported by a radiologist. The frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…In this study, we investigated the rate of incidental imaging findings detected in chest structures included in ACT images, which was 49.1%, similar to the rate of chest findings found incidentally in trauma patients recently [9]. The most common incidental finding in our patients was atelectatic changes (9.9%).…”
Section: Discussionsupporting
confidence: 60%
“…In this study, we investigated the rate of incidental imaging findings detected in chest structures included in ACT images, which was 49.1%, similar to the rate of chest findings found incidentally in trauma patients recently [9]. The most common incidental finding in our patients was atelectatic changes (9.9%).…”
Section: Discussionsupporting
confidence: 60%
“…Feedback to clinical teams following final reporting can increase the recognition of incidental findings by the ordering physician. 72…”
Section: Reporting Out To the Traumatologistmentioning
confidence: 99%
“…Especially in patients suffering from high-energy trauma, whole-body CT (WBCT) scans are increasingly used and recommended by guidelines due to their real-time detection of acute traumatic injuries (ATI) with high specificity and sensitivity and their widespread availability [ 1 , 2 , 3 , 4 ]. However, besides their associated radiation exposure [ 1 , 2 ], WBCT scans are likely to reveal incidental findings (IF) unrelated to the preceding trauma [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Incidental findings are defined as recently unknown abnormalities revealed unintentionally in medical examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the prevalence and impact of IFs in predominantly severely injured trauma patients who received WBCT or selective CT scans as initial emergency imaging modality [ 5 , 6 , 8 , 9 , 10 , 18 ]. The prevalence of IFs in different trauma patient populations varies from 30.4% to 75.3% [ 5 , 6 , 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 18 , 19 , 20 , 21 ], with more findings detected by means of WBCT than by selective CT scans [ 10 ]. An amount of 1% to 46.9% of IFs could have an impact on patients’ health and require urgent treatment or further examination [ 5 , 10 , 11 , 17 ].…”
Section: Introductionmentioning
confidence: 99%